1999
DOI: 10.1152/physrev.1999.79.2.325
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the Mammalian Respiratory System

Abstract: In this review, the maturational changes occurring in the mammalian respiratory network from fetal to adult ages are analyzed. Most of the data presented were obtained on rodents using in vitro approaches. In gestational day 18 (E18) fetuses, this network functions but is not yet able to sustain a stable respiratory activity, and most of the neonatal modulatory processes are not yet efficient. Respiratory motoneurons undergo relatively little cell death, and even if not yet fully mature at E18, they are capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
1
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(158 citation statements)
references
References 422 publications
(596 reference statements)
7
141
1
9
Order By: Relevance
“…Changes that occur in respiratory mechanisms as the foetus develops and becomes adult have been studied in several mammals (Hilaire and Duron, 1999), with emphasis on regulatory mechanisms, and the possible role of pacemaker neurons at successive stages (Del Negro et al, 2005;Peña et al, 2004). Maps of respiratory activity in newborn rat and mouse made with voltage sensitive dyes suggested that the respiratory activity started in each cycle on a discrete group of neurons located in the para-facial region, and then it was propagated caudally into the pre-Bötzinger complex level (Onimaru and Homma, 2003;Onimaru et al, 2004).…”
Section: Organisation Of Respiratory Neurons In Foetal Mousementioning
confidence: 99%
“…Changes that occur in respiratory mechanisms as the foetus develops and becomes adult have been studied in several mammals (Hilaire and Duron, 1999), with emphasis on regulatory mechanisms, and the possible role of pacemaker neurons at successive stages (Del Negro et al, 2005;Peña et al, 2004). Maps of respiratory activity in newborn rat and mouse made with voltage sensitive dyes suggested that the respiratory activity started in each cycle on a discrete group of neurons located in the para-facial region, and then it was propagated caudally into the pre-Bötzinger complex level (Onimaru and Homma, 2003;Onimaru et al, 2004).…”
Section: Organisation Of Respiratory Neurons In Foetal Mousementioning
confidence: 99%
“…In this context, it is noteworthy that we did not detect TUC-4 labeling in the ventral respiratory group of the early postnatal brainstem (P2), indicating that neuronal network formation and principal wiring have been completed at birth. Reorganization and adaptation of the synaptic architecture, however, have to be tailored to functional requirements during postnatal development (for review, see Hilaire and Duron, 1999;Richter and Spyer, 2001). Especially during the first 2 postnatal weeks, there are ongoing changes in the density of glutamate receptors on respiratory neurons (Liu and Wong-Riley, 2002).…”
Section: Putative Role Of Outwardly Rectifying Astrocytesmentioning
confidence: 99%
“…The nervous control of respiration that has been studied in vivo for several decades, mainly in adult cats, is now being studied in vitro in the neonatal rodent (Hilaire and Duron, 1999) because its respiratory network remains functional in vitro. There is little information regarding the in vivo respiration of the adult mouse (Tankersley et al, 1997(Tankersley et al, , 1999.…”
Section: Abstract: Breathing Patterns; Inspiratory Neuron and Motonementioning
confidence: 99%